Implementasi Kurikulum 2013 di SMK Kota Semarang - Wisudani Rahmaningtyas, Ismiyati, Ayunda, Nurul Izza (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2018)
The result of the observation showed that the teachers have prepared lesson plansaccording to the Curriculum 2013 guidelines, however the lesson plans has not been quiteimplemented in the learning process, in addition to the lack of the availability of theinfrastructures to support the learning process. The objective of the study was to determinethe extent to which the implementation of the Curriculum 2013 learning and the obstaclesencountered in the Archival subject by the teacher and students of 10th Office Administrationat SMK Negeri 9 Semarang. It was a qualitative research using the CIPP model of evaluationmethod. The results of the study showed that: 1) the mechanism of the lesson plansimplementation in archive learning has been in accordance with Curriculum 2013guidelines and the phases were complete. However, there were some inappropriateness, suchas the undelivered information about the scope of the subject matter and the assessmenttechnique, the lack of student involvement, and the absence of archive laboratory to supportthe learning process, 2) the obstacles in the implementation of the lesson plans in archivelearning were from three sources, i.e. the teacher, the students, and the infrastructure.